2016
DOI: 10.1074/mcp.m116.060129
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Cargo for Adaptor Protein (AP) Complexes 3 and 4 by Sucrose Gradient Profiling

Abstract: Intracellular vesicle trafficking is a fundamental process in eukaryotic cells. It enables cellular polarity and exchange of proteins between subcellular compartments such as the plasma membrane or the vacuole. Adaptor protein complexes participate in the vesicle formation by specific selection of the transported cargo. We investigated the role of the adaptor protein complex 3 (AP-3) and adaptor protein complex 4 (AP-4) in this selection process by screening for AP-3 and AP-4 dependent cargo proteins. Specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 49 publications
2
15
0
Order By: Relevance
“…We could demonstrate that GFP‐fusions of the tonoplastic proteins MOT2, as well as NRAMP3 and NRAMP4, are partially missorted to the PM and to intracellular compartments in ap4ß‐1 and ap4μ mutants, while GFP‐INT1 is not, and that a WT‐like distribution is re‐established in stable transformants of ap4μ expressing AP4μ Pro :AP4μ‐GUS. Partial missorting of NRAMP3 and NRAMP4 in ap4 mutants might contribute to reduced chlorophyll contents and to depletion of cytochrome p450 proteins in ap4 mutants reported earlier, either by impairing the release of iron from the vacuole, or by disturbing iron distribution between cells or tissues via mislocalized NRAMP3, and particularly NRAMP4. This could explain why stable overexpression of NRAMP4‐GFP in ap4μ plants did not complement chlorophyll concentration of seedlings grown on iron‐deficient medium (Figure S1 in Appendix S1).…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…We could demonstrate that GFP‐fusions of the tonoplastic proteins MOT2, as well as NRAMP3 and NRAMP4, are partially missorted to the PM and to intracellular compartments in ap4ß‐1 and ap4μ mutants, while GFP‐INT1 is not, and that a WT‐like distribution is re‐established in stable transformants of ap4μ expressing AP4μ Pro :AP4μ‐GUS. Partial missorting of NRAMP3 and NRAMP4 in ap4 mutants might contribute to reduced chlorophyll contents and to depletion of cytochrome p450 proteins in ap4 mutants reported earlier, either by impairing the release of iron from the vacuole, or by disturbing iron distribution between cells or tissues via mislocalized NRAMP3, and particularly NRAMP4. This could explain why stable overexpression of NRAMP4‐GFP in ap4μ plants did not complement chlorophyll concentration of seedlings grown on iron‐deficient medium (Figure S1 in Appendix S1).…”
Section: Discussionmentioning
confidence: 77%
“…plants to test for potential additive effects, and established stably transformed ap4μ mutants expressing the genomic sequence of AP4μ fused to GUS or GFP under control of the AP4μ ‐promoter ( ap4μ/AP4μ Pro :AP4μ‐GFP and ap4μ/AP4μ Pro :AP4μ‐GUS ) as complementation lines. Measurement of primary root lengths revealed that, identical to ap4ß‐1 mutants, ap4ß‐2 and ap4μ mutants also developed significantly shorter roots compared to the WT (Figure A). Moreover, all single and double k.o.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations